Physicians' level of hindrance by body hair in dermatoscopy and clinical benefit of an automated hair removal algorithm - Müller-Christmann, Christine; Uhlmann, Lorenz; Vogt, Karsten; Schneiderbauer, Roland; Menzer, Christian; Toberer, Ferdinand; Schank, Timo Emanuel; Enk, Alexander; Hänßle, Holger (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
Background and objectives Dermatoscopy may be hindered by body hair, and the development of an automated hair removal algorithm (AuHRA) might improve the diagnostic accuracy. However, the physicians' exact level of hindrance and the clinical benefit attained by AuHRA has not been assessed. The objectives of this study are to quantify the physicians' level of hindrance by body hair and the level of improvement in the visibility of underlying dermatoscopic patterns after application of AuHRA to digital images of hair-covered nevi. Patients and methods A cross-sectional reader study including 59 sets of dermatoscopic images of benign nevi that were presented to six dermatologists. Each set included three images of one individual nevus (unshaved/physically shaved/digitally shaved with AuHRA), which were compared to each other within each set to assess the level of improvement caused by hair removal. Results In comparison to unshaved lesions, dermatologists attributed the highest mean level of improvement to a physical shave (+1.36, p < 0.001) followed by AuHRA's digital shave (+0.79, p < 0.001). The majority of dermatologists considered the application of AuHRA as helpful and confirmed a medical need. Conclusions The dermatologists in our study confirmed a substantial impairment of the dermatoscopic examination by body hair. We demonstrated a clinical benefit attained by AuHRA in comparison to unshaved or physically shaved lesions.